Leaving the Lectures Behind: Using Community-Engaged Learning in Research Methods Classes to Teach about Sustainability. (April 2023) - Soyer, Mehmet; McCrackin, Gina; Ziyanak, Sebahattin; Givens, Jennifer; Jump, Vonda; Schad, Jessica
This article explores the outcomes of using community-engaged learning in a sustainability-focused social sciences research course titled Methods of Social Research. The integrated components of the course were designed to teach students about the research process while addressing sustainability issues at Utah State University. Throughout the course, students learned how to collect, analyze, and interpret data; work in research teams; write a grant; and write and present a final research paper. Student sustainability surveys and the final course evaluation were used to analyze student learning outcomes. We found that students demonstrated increased confidence in collecting, analyzing, and interpreting data and an improved effectiveness and enjoyment in working in teams toward a final product. Students also exhibited their knowledge of small- and large-scale sustainability challenges as well as a decisiveness in answering questions related to sustainability. These outcomes resulted in heightened student self-efficacy and critical thinking skills when performing research and engaging with issues related to sustainability.